Reaction time and special fitness in tennis players aged 10-12 years - Waldzinski, T. (Archives of Budo Science of Martial Arts and Extreme Sports, 2023)
Background & Study Aim: Reaction time is the time elapsed from the stimulus (nerve impulse) to the initiation of movement. This ability involves performing a deliberate motor action in the shortest possible time, utilizing the entire body or a specific part of it. Excellent speed and short reaction time are among the most essential elements of modern tennis. A lightning-fast start towards the ball, quick decision-making during returns or volleys (especially in doubles matches) can contribute to high performance in tennis. Recent match analyses of the world's top tennis players have shown that speed is the motor skill that distinguishes the exceptional among the best players. The aim of this study was knowledge about the relationship between reaction time and special fitness in tennis players aged 10-12 years.